2017
DOI: 10.1038/s41598-017-07698-4
|View full text |Cite
|
Sign up to set email alerts
|

Colony stimulating factor-1 in saliva in relation to age, smoking, and oral and systemic diseases

Abstract: Colony stimulating factor (CSF)-1 is a growth factor that stimulates the survival, proliferation and differentiation of mononuclear phagocytes, which has been implicated in several inflammatory diseases. This study evaluated the possible influence of age, sex, smoking, periodontitis, caries, and several systemic conditions on salivary levels of CSF-1. Four-hundred and forty-one individuals were enrolled in this study. All participants answered a health questionnaire and underwent a comprehensive oral examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
26
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 48 publications
7
26
1
1
Order By: Relevance
“…This difference is important to determine since early intervention and removal of etiology will reverse mucositis [19,21]. A positive correlation between CSF-1 and IL-1β levels in both saliva and PICF was seen, which is in accordance with previous work from our group [12]. CSF-1 regulates the production, maintenance, and function of cells from the mononuclear phagocyte lineage, as well as the function of other cells expressing the CSF-1R [5].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This difference is important to determine since early intervention and removal of etiology will reverse mucositis [19,21]. A positive correlation between CSF-1 and IL-1β levels in both saliva and PICF was seen, which is in accordance with previous work from our group [12]. CSF-1 regulates the production, maintenance, and function of cells from the mononuclear phagocyte lineage, as well as the function of other cells expressing the CSF-1R [5].…”
Section: Discussionsupporting
confidence: 87%
“…Blockage of the CSF-1 receptor (CSF1R) has been shown to result in reduced alveolar bone loss [8]. We have previously reported CSF-1 and IL-34 are altered in saliva from periodontitis patients [12,13]. However, their levels in peri-implant diseases have not been explored yet.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding CSF‐1, a trend toward elevated levels in serum from patients with AgP was seen, whereas its levels in saliva did not differ among groups. Authors of the current study recently reported lower CSF‐1 levels in serum from patients with CP, 18 and higher CSF‐1 levels in saliva from patients with CP have repeatedly been observed 18,19 . However, age could possibly be introduced as a confounder, as patients with AgP are often younger.…”
Section: Discussionmentioning
confidence: 62%
“…However, age could possibly be introduced as a confounder, as patients with AgP are often younger. The authors also found an increase in salivary CSF‐1 levels with age, 19 which could affect results. Explanations for discordant results between CP and AgP might reside in immunologic differences between the two disease groups, and therefore, the addition of a CP group in this study would have been ideal.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation